If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + x + x = 44 Combine like terms: x + x = 2x 2x + x + x = 44 Combine like terms: 2x + x = 3x 3x + x = 44 Combine like terms: 3x + x = 4x 4x = 44 Solving 4x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 11 Simplifying x = 11
| 1e+18= | | x/6=3/9 | | -2(4s-5)-10=-3(5s+5)-5 | | 3n+3=-4 | | 123456789-987654321=0 | | (9-10)x= | | -6x^2+5x+6=7.01466 | | 1x+1-2-(3-x)=6-(1-1) | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | 17-x=33(x+7) | | 6-2(3x-4)=12 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | 3t+4=16 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | -6x^2+5x+6=1.41666 | | -3+6x=5x-13 | | 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 | | -3+6x=5x-13 | | 9(x-8)+28=9x-44 | | 6/7*7/8 | | 27+2x+5+3x-4=180 | | -9(9+u)-2u=-10 | | 3t+4+t=6 |